Primary Extracranial Meningiomas of the Sinonasal Tract: A Systematic Review - Goh, Xin L.; Chee, Justin Rui Tzen; Tham, Alex C. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Background Primary extracranial meningiomas (PEMs) of the sinonasal tract with no intracranial extension are rare. Our study presents the largest systematic review to date, providing a comprehensive overview and comparison of the characteristics, treatment, and prognosis of PEMs, with comparison to primary intracranial meningiomas (PIMs).Methods A systematic review was conducted according to the PRISMA guidelines on PubMed, Embase, and Google Scholar up to November 1, 2022. A total of 70 documented cases from 64 articles were included. Data analysis was performed to compare low-grade (World Health Organization [WHO] Grade I) and high-grade (Grade II, III) PEMs.Results Majority of patients were symptomatic with nasal symptoms (72.1%), followed by eye symptoms (41.2%) and facial swellings (41.2%). The nasal cavity was the most commonly affected site (70.0%). Most tumors were WHO Grade 1 (87.5%) with meningothelial histological subtype. PEMs have a predilection for involvement of surrounding structures, with more than half reporting erosion of sinonasal walls or orbital involvement (64.3%). Despite so, PEMs have a favorable prognosis, with high survival rates (95.3%) and low rate of recurrence (8.5%). Mainstay of treatment is surgical resection (98.6%). A total of 69/70 cases (98.6%) underwent surgical resection.Conclusions There are no clear defining clinical features of PEMs; hence, it is imperative for clinicians to prioritize histological diagnosis to guide further management. A conclusive diagnosis of PEMs, i.e., exclusion of PIMs, requires imaging and potential intraoperative assessment. Its prognosis is likely dependent on both WHO grading and the ability to achieve complete surgical extirpation. Endoscopic resection is recommended even in high-grade PEMs for localized and resectable disease. Radiotherapy may be reserved for unresectable or recurrent tumors as salvage therapy.
Keywords: paranasal sinuses; meningioma; head and neck neoplasm